Ethical challenges of researching emergent socio-material-technological phenomena: insights from an interdisciplinary mixed-methods project using mobile eye-tracking - Kaufmann, Katja; Bork-Hüffer, Tabea; Gudowsky, Niklas; Rauhala, Marjo; Rutzinger, Martin (Journal of information, communication and ethics in society, 2021)
This paper aims to discuss research ethics in mixed-methods research (MMR) and MMR development with a focus on ethical challenges that stem from working with technical instruments such as mobile eye-trackers.,The case of an interdisciplinary mixed-methods development study that aimed at researching the impacts of emerging mobile augmented-reality technologies on the perception of public places serves as an example to discuss research-ethical challenges regarding (1) the practical implementation of the study, (2) data processing and management and (3) societal implications of developing instruments to track and understand human practices.,This study reports challenges and experiences in ethical decision-making in the practical implementation of the study regarding the relationship to research subjects, the use of mobile research instruments in public places and the interdisciplinary cooperation among research team members. Further, this paper expounds on ethical challenges and recommendations in data processing and management and with a view to societal implications of method development and the aspirations of transdisciplinarity. This study concludes that institutionalized ethics need to become more flexible, while applied ethics and reflection must make their entry into university curricula across disciplines.,Complex interdisciplinary mobile and mixed-methods projects that involve sensors and instruments such as mobile eye-trackers are on the rise. However, there is a significant lack of engagement with practical research ethical challenges, practices and requirements in both mixed-methods and method-development literature. By taking a context- and process-oriented perspective focusing on doing ethics, the paper contributes a concrete empirical case to these underdeveloped fields.
Gesehen am 14.04.2025
Online veröffentlicht: 10. July 2021